2021
DOI: 10.48550/arxiv.2102.01948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A search for radio afterglows from gamma-ray bursts with the Australian Square Kilometre Array Pathfinder

James K. Leung,
Tara Murphy,
Giancarlo Ghirlanda
et al.

Abstract: We present a search for radio afterglows from long gamma-ray bursts using the Australian Square Kilometre Array Pathfinder (ASKAP). Our search used the Rapid ASKAP Continuum Survey, covering the entire celestial sphere south of declination +41 β€’ , and three epochs of the Variables and Slow Transients Pilot Survey (Phase 1), covering ∼ 5, 000 square degrees per epoch. The observations we used from these surveys spanned a nine-month period from 2019 April 21 to 2020 January 11. We crossmatched radio sources foun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 76 publications
(95 reference statements)
0
4
1
Order By: Relevance
“…The flux detected for GRB 171205A Leung et al (2021) prior to the latest non-detection reported here does not meaningfully constrain the possible collapsar ejecta mass. If we assume that the latest detection at ∼ 900 days after the GRB is fully from the collapsar ejecta, i.e.…”
Section: Constraints On the Ejecta Masscontrasting
confidence: 66%
See 4 more Smart Citations
“…The flux detected for GRB 171205A Leung et al (2021) prior to the latest non-detection reported here does not meaningfully constrain the possible collapsar ejecta mass. If we assume that the latest detection at ∼ 900 days after the GRB is fully from the collapsar ejecta, i.e.…”
Section: Constraints On the Ejecta Masscontrasting
confidence: 66%
“…Assuming a constant-density interstellar medium around the collapsars, we found that ejecta with 0.2 M mass are inconsistent with observations for our fiducial model. Considering GRB 171205A and a wind profile for the circum-burst density (Leung et al 2021), we obtain a mass constraint of 0.5 M ( 0.05 M ) for 1 pc (0.01 pc) assumed shock termination radius.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations